Gaming : essays on algorithmic culture - Galloway, Alexander R., 1974- (Electronic mediations ;, 2006)
In Gaming, Alexander R. Galloway considers the video game as a distinct cultural form that demands a new and unique interpretive framework. Using examples from more than fifty video games, Galloway constructs a classification system of action in video games, and, ultimately offers a new conception of gaming and, more broadly, of electronic culture, one that celebrates the qualities of the digital age.